Panorama of Long Bay Rifle Range, Randwick, New South Wales, 1 - EB Studios (Sydney, N.S.W.) (1917)
Panorama showing the buildings and military tents and men at practice on the range.
Title devised by cataloguer from acquisition documentation.
Part of collection: Enemark collection of panoramic photographs.
Also available online
Keywords: Rifle-ranges -- New South Wales -- Randwick -- Photographs; Rifle practice -- New South Wales -- Randwick -- Photographs; Randwick (N.S.W.) -- Buildings, structures etc. -- Photographs